Comparison of Frequency‐Domain Electromagnetic Responses at Different Offsets Based on Exact Calculation of Grounded‐Wire Source. Issue 1 (4th January 2022) - Xue, Guoqiang; Zhou, Nannan; Hou, Dongyang
Abstract: Subsurface geoelectric structures and resources can be detected based on the propagation of the electromagnetic field. Near‐source electromagnetic methods have recently become the most popular survey mode. However, calculation of the electromagnetic field in the near‐source region with artificial sources has always been performed based on far‐source dipole approximation. Owing to the introduction of artificial sources in the near‐source region, it is challenging to obtain accurate solution of the electromagnetic field based on the relationship between the observation point and the source, thereby affecting the detection accuracy. Specifically, the main problem lies in the position vector of the transmitting source, which is generally neglected in the response calculation based on the plane‐wave theory. Moreover, only far‐source data can be observed in the plane‐wave theory. However, near‐source data have been collected in a near‐source survey, with the dipole approximation resulting in a large error. We introduce a point charge element to decrease or eliminate the error caused by the dipole approximation. The non‐homogeneous Helmholtz equation is first solved using the Green's function. Then, the response expression of the real source, including the source position vector, is obtained by integrating the response of the harmonic point charge element. The substitution of the dipole elements with the point‐charge elements not only reduces the dipole approximation errors but also displays the electromagnetic characteristics of the entire zone, which are verified by the forward modeling and field survey results. The near‐source (offset is 0.8 of the target depth) survey can be realized based on the point charge element. Key Points: A point charge element is introduced to decrease or eliminate the error caused by dipole approximation The response expression of the real source, including the source position vector, is derived The electromagnetic characteristics of the entire zone are displayed